Computer algebra and applications - Domarkas, Aleksas; Rakauskas, Rimantas-Jonas; Pincevičius, Albertas (Lietuvos matematikos rinkinys, 2002)
Short review of computer algebra systems Macsyma, Maple, Derive, Mathematica, MuPad, Maxima.